The welfare state and support for environmental action in Europe - Parth, Anne-Marie; Vlandas, Tim (Sage, 2022)
How do welfare state policies affect the political support for environmental action of economically vulnerable social groups? Two competing hypotheses can be delineated. On the one hand, a synergy logic would imply that welfare state generosity is associated with higher support for environmental action among economically vulnerable groups due to the insecurity reducing effects of the welfare state. On the other hand, a crowding-out logic would suggest that welfare state generosity is associated with lower support for other policy priorities like environmental action. We test these two hypotheses using 2019 Eurobarometer survey data and country-level indicators of welfare state generosity in 22 European countries.We find that the working class and the elderly are particularly opposed to individual and national environmental action and that the welfare state plays a complex moderating role. Consistent with a synergy logic, welfare state generosity increases pro-environmental behaviour among the working class, but its association with more positive attitudes towards national environmental policies is less strong. Consistent with a crowding-out logic, the elderly appear less likely to behave in environmentally friendly ways if retirement benefits are high. To explore the mechanisms behind this association, we show that the working class who struggle to pay their bills are most opposed to environmental action. Overall, economic insecurities are key obstacles for support of environmental actions and the effects of thewelfare state depend both onwhich social group is concerned and whether individual behaviour versus policy preferences are considered.